Diagnostic accuracy of percutaneous biopsy in retroperitoneal sarcoma. Issue 4 (24th January 2019) - Almond, L M; Tirotta, F; Tattersall, H; Hodson, J; Cascella, T; Barisella, M; Marchianò, A; Greco, G; Desai, A; Ford, S J; Gronchi, A; Fiore, M; et al.
Abstract: Background: Percutaneous biopsy is recommended before surgery for suspected retroperitoneal sarcoma (RPS) to confirm the histological diagnosis and guide surgical strategy. The present study aimed to establish the diagnostic accuracy of percutaneous core biopsy with respect to histological diagnosis and tumour grade. Methods: Data on patients with suspected RPS who underwent percutaneous biopsy followed by surgical resection between 2005 and 2016 at one of two tertiary European sarcoma units were reviewed. Histological tumour type and tumour grade on biopsy were correlated with postoperative histology to evaluate diagnostic accuracy. Results: A total of 239 patients underwent percutaneous core biopsy followed by surgical resection in Milan (163, 68·2 per cent) or Birmingham (76, 31·8 per cent). Diagnostic accuracy varied with histological diagnosis ( P < 0·001), but demonstrated overall concordance with final pathology following resection in 67·2 per cent of biopsies (κ = 0·606). The majority of discrepancies occurred in dedifferentiated liposarcoma (DDLPS), owing to under-recognition of dedifferentiation in this group. Concordance between pathology on biopsy and resection improved to 81·1 per cent when DDLPS and well differentiated liposarcoma were grouped together as liposarcoma. Grade on biopsy was concordant with grade on resection specimen in 60·4 per cent of tumours (κ = 0·640). Diagnosis of high-grade tumours on biopsy had a high specificity (98 per cent), and moderate positive predictive value (85 per cent) and negative predictive value (78 per cent). Conclusion: A diagnosis of DDLPS or leiomyosarcoma on percutaneous biopsy is highly reliable. High-grade sarcomas can be identified with high specificity, which opens the door to a study on neoadjuvant therapy in these patients. Abstract : Weak for liposarcoma